Detailed retinal phenotype of Boucher-Neuhäuser syndrome associated with mutations in PNPLA6 mimicking choroideremia. (4th May 2019) - O'Neil, Erin; Serrano, Leona; Scoles, Drew; Cunningham, Kayla E; Han, Grace; Chiang, John; Bennett, Jean; Aleman, Tomas S.
ABSTRACT: Purpose : To confirm the pathogenic role of a novel mutation in PNPLA6 and detail the phenotype of a patient presenting with choroideremia-like chorioretinal degeneration. Methods : A 40-year-old man with presumed choroideremia underwent a complete ophthalmic examination, full-field electroretinography (ERG), kinetic fields and two-color automated static perimetry and retinal imaging with spectral domain optical coherence tomography (SD-OCT) and near-infrared (NIR) and short wavelength (SW) fundus autofluorescence (FAF). Results : Visual acuity was 20/200 and 20/40 for the right and left eye, respectively, with a ~ 5D myopic correction. Small cone-mediated ERG responses were detectable. The visual field by kinetic perimetry (V-4e stimulus) was limited to small (<5°) central islands separated from large peripheral islands of vision by an absolute midperipheral scotoma. There were minute islands of apparently spared retina near the foveal center separated from large peripheral islands of better appearing retina by severe pericentral and midperipheral chorioretinal atrophy. SD-OCT confirmed detectable photoreceptors near the center and in nasal midperipheral retina despite severe outer segment loss. Central photoreceptor loss was associated with disproportionately severe retinal pigment epithelium (RPE) depigmentation and choroidal atrophy. NIR- and SW-autofluorescence was widely hypoautofluorescent with the exception of residual autofluorescence along peripheral regions of relative RPE preservation. Gene screening revealed biallelic mutations (p.Arg1031GlnfsTer38/p.Arg1183Gln) in PNPLA6 . Hypogonadotropic hypogonadism and cerebellar vermis hypoplasia by MRI confirmed a diagnosis of Boucher-Neuhäuser syndrome. Conclusions : PNPLA6 -associated retinal degenerations can present with predominantly retinal findings and subtle systemic abnormalities and should be considered in the differential diagnosis of diffuse chorioretinal atrophies.